Identification and characterization of CIP2A as a novel oncogenic inhibitor of PP2A - Niemelä, Minna (Annales Universitatis Turkuensis D 1032, 2012)
Inhibition of the tumor suppressor protein phosphatase 2A (PP2A) activity has been identified as one of the five key alterations required for human cell transformation. Regardless of this crucial role in human cancer development, the detailed mechanisms by which PP2A inhibition occurs in human cancers remain largely uncharacterized. PP2A regulates a plethora of cellular signaling cascades. One of the targets of PP2A is Myc oncoprotein, which is destabilized and degraded in response to PP2A-mediated dephosphorylation of Myc serine 62. In this study we identify Cancerous Inhibitor of PP2A (CIP2A) as a previously uncharacterized endogenous inhibitor of PP2A in human cancer cells. CIP2A inhibits PP2A activity leading to subsequent stabilization of the Myc protein. CIP2A promotes malignant growth of cancer cells in vitro and xenograft tumor formation in vivo and is overexpressed in cancer. Moreover, we explored the effect of CIP2A on global transcriptional profiles and validated a CIP2A-dependent transcriptional signature. Analysis of the CIP2A signature revealed both Myc-dependent and -independent functions for CIP2A. Importantly, we demonstrate that the CIP2A signature has clinical relevance in human breast cancer subtypes. Finally, we identify the genes potentially mediating the long-term growth suppression in CIP2A depleted cancer cells. Taken together, this work identifies CIP2A as a novel human oncoprotein and describes its function in cancer cells. These results may open novel possibilities for patient stratification and therapeutic intervention of cancer.